A remote sensing-based evaluation of an ungauged drainage basin in Southwestern Nigeria. Issue 3 (2nd July 2020) - Eludoyin, Adebayo Oluwole; Adewole, Adedayo Oreoluwa
ABSTRACT: Paucity of scientific information about many river basins in developing countries, especially in sub-Saharan Africa, has been linked to poor datasets and expensive monitoring technology. This study assessed the capability of freely available Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER), Shuttle Radar Topography Mission (SRTM) Digital Elevation Models (DEMs) and Landsat imageries to provide management decision support on river basins in the region. Main objectives are to examine landuse/landcover change over the Opa river basin in Ife area in southwest Nigeria, characterize the basin morphometrically and compare the morphometric characteristics from different sensors and resolutions. Results showed that the ecosystem of the river basin is vulnerable to urban intrusion and disturbance from human activities as urban population increases. Also, analysis of the DEMs allowed the drainage basin to be delineated into relatively homogenous and manageable sizes that can ease management, organization and evaluation of their eco-hydrological systems. The study concluded that complementary use of SRTM and ASTER DEMs with Landsat imageries that are freely available spatial data for researchers, is capable of providing useful decision support system for management of river basins in the region, to a level of uncertainty occasioned by sensors' characteristics.